Optimization Of Potassium Hydroxide (KOH) Etching On The Fabrication Of P-Type Silicon Nanowire Transistor Patterned By Atomic Force Microscopy Lithography - Abdullah, Ahmad Makarimi (2012)
Silicon nanowire transistor (SiNWT) has been successfully fabricated by atomic force microscopy (AFM) lithography through wet etching process. The silicon on insulator (SOI) <100> wafer was used as a starting material. Prior to use, the SOI wafer was cleaned by using ammonium hydroxide (NH4OH), hydrogen peroxide (H2O2), nitric acid (HNO3) and Di-Ionize water (DIW) and diluted hydrofluoric acid (HF) to remove the organic, inorganic contaminants and native oxide from the wafer surface. A non-contact AFM mode was chosen to perform the AFM lithography process on pre-cleaned SOI wafer. The SiNWT structure was designed by using raster programming. A conductive AFM tip (Cr/Pt cantilever tip) was used to fabricate SiNWT patterns on the SOI surface based on pre-designed structures.